2010
DOI: 10.5116/ijme.4ba1.4034
|View full text |Cite
|
Sign up to set email alerts
|

Educational environment of university and non-university hospitals in Japan

Abstract: Objectives: The greater satisfaction of residents in non-university hospitals in Japan found in a previous survey may reflect a better educational environment in these hospitals compared to university hospitals. We aimed to compare the educational environment of university hospitals and non-university hospitals. Methods: A cross-sectional survey was sent to 6725 1st year resident physicians. The Postgraduate Hospital Educational Environment Measure (PHEEM) was used as a reliable and validated instrument to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…When this national policy of 2-year postgraduate residency training programs was introduced in 2004, the computer-based national matching system was introduced and students could apply to their preferred hospitals throughout the entire country 2. In our previous study, the greater satisfaction of non-university residents was shown compared with university residents in Japan 3. In that study, to compare the educational environments of university and non-university hospitals, we used the Postgraduate Hospital Educational Environment Measure (PHEEM), which is a 40-item inventory, and an evaluation tool consisting of a validated questionnaire with three subscales.…”
Section: Introductionmentioning
confidence: 94%
“…When this national policy of 2-year postgraduate residency training programs was introduced in 2004, the computer-based national matching system was introduced and students could apply to their preferred hospitals throughout the entire country 2. In our previous study, the greater satisfaction of non-university residents was shown compared with university residents in Japan 3. In that study, to compare the educational environments of university and non-university hospitals, we used the Postgraduate Hospital Educational Environment Measure (PHEEM), which is a 40-item inventory, and an evaluation tool consisting of a validated questionnaire with three subscales.…”
Section: Introductionmentioning
confidence: 94%
“…In terms of issues about gifts and honesty, many more residents in community teaching hospitals provided the greater number of acceptable responses than those in university hospitals. After introduction national mandatory residency program by Japanese Ministry of Health, Labour and Welfare, community teaching hospitals improved their educational environments which were proved to be better than those of university hospitals [ 14 ]. The better hospital educational environment included appropriate behaviors related to professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…Many Japanese physicians also report that they are concerned with their inadequate training in this area [ 11 ]. However in the years surrounding our 2005 survey, Japan introduced a national mandatory residency program and we noted that teaching hospitals improved their educational environments, including appropriate behaviors related to professionalism [ 14 ], but little additional information is available on the explicit evaluation of medical professionalism among Japanese physicians.…”
Section: Introductionmentioning
confidence: 99%
“…12 There were few auscultation skill courses provided by cardiology division in most teaching hospitals in Japan. 12,13 Thus, although cardiology fellows and faculty have relatively higher individual skills about cardiac auscultation, their rotating junior doctors are likely to have little chance to improve the skills. Since many faculty physicians of the department of general internal medicine in teaching hospitals in Japan are interested in teaching cardiac auscultation for residents, 14 rotation training in this department may provide precious opportunity to learn cardiac auscultation for junior doctors.…”
Section: Pre-and Post-testmentioning
confidence: 99%